2015
DOI: 10.4014/jmb.1409.09088
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging Activities of Tannin Extracted from Amaranth (Amaranthus caudatus L.)

Abstract: This study investigates the bioactivity of tannin from amaranth (Amaranthus caudatus L.) extracts. The antioxidant activities of the extracts from amaranth leaves, flowers, and seeds were evaluated. Tannin from leaves of amaranth has been evaluated for superoxide scavenging activity by using DPPH and ABTS(+) analysis, reducing power, protective effect against H2O2-induced oxidative damage in L-132 and BNL-CL2 cells, and inhibition of superoxide radical effects on HL-60 cells. At a concentration of 100 μg/ml, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Previously, Jo et al . 43 and Enujiugha et al . 41 respectively had reported lower values of proanthocyanidin (0.516 ± 0.02 and 0.045 ± 0.000 mg TAE/g) in A. caudatus using the tannic acid standard as opposed catechin standard used in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, Jo et al . 43 and Enujiugha et al . 41 respectively had reported lower values of proanthocyanidin (0.516 ± 0.02 and 0.045 ± 0.000 mg TAE/g) in A. caudatus using the tannic acid standard as opposed catechin standard used in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Tannins function as an astringent that can cause narrowing of the pores of the skin, harden the skin and act as an antimicrobial and antifungal so as to prevent secondary infection in the wound. Tannins are polyphenols with strong antioxidant activity that can protect against damage to free radicals caused by UV exposure and reduce the risk of skin cancer (25). Tannins are able to reduce the production of H2O2, inhibits the induction of ornitine decarboxylase and stimulates DNA synthesis in the epidermis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Amaranth grain has the potential to contribute to improving the nutrition of populations, especially in developing countries, because it has nutritional and functional properties (Muyonga et al, 2008). The presence of some compounds has been reported, such as phenols, fatty acids, tocopherols, carotenoids and others that contribute to health, reducing the risk of oxidative stress related to chronic diseases (Jo et al, 2015;López et al, 2013;Tang & Tsao, 2017). However, several researchers have demonstrated that amaranth seeds may contain antinutritional compounds, which could affect their nutritional value and limit their use.…”
Section: Discussionmentioning
confidence: 99%